The Influence of DDAVP Infusion on the Coagulation and Fibrinolytic Response to Surgery - Melissari, E; Scully, M F; Paes, V; Ellis, V; Kakkar, V V (Thrombosis and Haemostasis, 1986)
The response of components of the coagulation and fibrinolysis systems to infusion of DDAVP has been examined in patients undergoing elective surgery. In the DDAVP treated group there was a significant increase, compared to control, in plasminogen activator (by fibrin plates p <0.005, ECLT p <0.0125, by Student’s t test) before operation. No difference between groups was seen by either methods in the activator levels in samples 24 h postoperation, whereas a significant drop (p <0.002) in protein C concentration was observed at this stage in the treated group. Levels of factor VIII components were significantly higher (p <0.005) than control at all stages of operation and a significant shortening (5 sec p <0.05) of the APTT was seen at all stages (apart from 24 h samples). DDAVP infusion therefore may exacerbate the hypercoagulable state observed in surgical patients without preventing the (post-operatively) fibrinolytic shutdown. Instead, infusion tends to produce fibrinolytic depletion at the key mid-operative stage.
Keywords: Plasminogen activator; Factor VIII components; Protein C; Haemostasis; DDAVP